1999
DOI: 10.1111/j.1744-7348.1999.tb05239.x
|View full text |Cite
|
Sign up to set email alerts
|

Severity of infection of Moroccan barley yellow dwarf virus PAV isolates correlates with variability in their coat protein sequences

Abstract: SummaryBiological properties and deduced amino acid sequences of the overlapping coat and 17kDa proteins were compared for 12 barley yellow dwarf virus PAV‐type isolates collected at different locations in Morocco. The biological variability of the 12 isolates was investigated by inoculation to a set of as many as eight barley cultivars and an oat cultivar. Significant biological variability was observed among the Moroccan PAV–type isolates, with the isolates falling into two clusters. Cluster 1 contained isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
1
21
1
Order By: Relevance
“…Another species of BYDV, PAS, produces more severe symptoms on susceptible and resistant varieties of oat (Chay et al. , 1996) and barley (Bencharki et al. , 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another species of BYDV, PAS, produces more severe symptoms on susceptible and resistant varieties of oat (Chay et al. , 1996) and barley (Bencharki et al. , 1999).…”
Section: Introductionmentioning
confidence: 99%
“…, 1996; Mastari et al. , 1998; Bencharki et al. , 1999), PAV and PAS share the same vector species – Rhopalosiphum padi and Sitobion avenae .…”
Section: Introductionmentioning
confidence: 99%
“…PAV MA9508, Fig. 1) with PAV-129, and five isolates with PAVs from Japan, USA, and Australia [1]. Only PAV-like isolates were found in Illinois [19].…”
Section: Discussionmentioning
confidence: 97%
“…Most likely, BYDV-PAS will be found in other geographical regions as well. The lack of PAV-like isolates in South Central Alaska is not understood, especially since PAS-like isolates have always been detected with PAV isolates (same site but different plants) in France, New York, and Morocco [1,3,14]. Although the PAS-like isolates did not have a host preference relative to barley and oats in Alaska, Masteri et al [14] detected a definite PAS preference for barley over ryegrass in France, and Chay et al [3] only found the PAS in maize and winter wheat in New York.…”
Section: Discussionmentioning
confidence: 99%
“…Based on sequencing, BYDV-PAV was initially subdivided into two subgroups, A and B, with about 90 % amino acid sequence homology in the CP gene. The B group nowadays has been identifi ed as BY-DV-PAS and cannot be distinguished from BYDV-PAV by serology, but is differentiated by restriction pattern analysis (Bencharki et al, 1999;Mastari et al, 1998). Other species could be distinguished after cleavage with HinfI (Du et al, 2007).…”
Section: Discussionmentioning
confidence: 99%